The challenges of IBS transportation in rural areas in Perak / Alia Shaheera Ain Kamaruddin and Nor Diana Aziz - Kamaruddin, Alia Shaheera Ain; Aziz, Nor Diana (2023)
The Fourth Industrial Revolution (Industry 4.0) has prompted the development of the Construction Strategy Plan 4.0 to emphasize the usage of prefabrication such as Industrialized Building System (IBS). However, the rate of IBS adoption in Malaysia is still below the government’s target despite its introduction in the 1960s. The implementation of IBS is impeded as underdeveloped road infrastructure proves to cause transportation constraints. Furthermore, the overloaded heavy vehicles of IBS transportation cause damage to the road infrastructure, further hindering the usage of IBS. This paper highlights the challenges of IBS transportation in rural areas through interview sessions with experienced individuals in the construction industry. The interviews aim to identify the issues regarding transport in rural areas and suggest methods of improvement towards the accessibility of IBS transportation. The research concludes that the design of roads plays an essential role in the efficiency of transit of prefabricated components.